SUKUM 43rd officially close - UMP, PNC (2018)
Kuantan, 18 August – Universiti Malaysia Pahang marked the end of the 43rd Intervarsity Staff Sport (SUKUM) with a colourful closing ceremony at the Astaka Hall in UMP Gambang campus. Deputy Vice-Chancellor (Research & Innovation), Prof. Dato’ Dr. Mashitah Mohd Yusoff 0fficially closed the 43rd SUKUM on behalf of the Vice-Chancellor.